Efektivitas Pengelolaan Alokasi Dana Desa Tahun 2017 dalam Upaya Peningkatan Kesejahteraan Masyarakat di Desa Hessa Perlompongan Kecamatan Air Batu Kabupaten Asahan - Dian Nur Utama Saragih; Abdul Kadir; Walid Musthafa (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2022)
Welfare society to be important to note the increase because it is the aspiration of the implementation of the country, this would be a great responsibility, especially for the Government of the Village because it has the authority of the area in the implementation of the government in Indonesian. One of the efforts made by the Government in improving the welfare of society is to provide Allocation of Village Funds every year to each of the respectively the one who is the Hessa Perlompongan in the Air Batu of the Asahan regency of North Sumatera, which is in 2017. The management Allocation of Village Funds for the year 2017 at the Hessa Perlompongan have been set up in a regulation of the Asahan No. 8 Year 2017 Guidelines for Management Allocation Fund of the year 2017 and make improving the welfare of society as one of the goals of its management. Based on this is a writer interested in doing research with the title of the Effectiveness Allocation Fund of the year 2017 In The Improvement of Public Welfare Society in the village of Hessa Perlompongan the Air Batu of the Asahan Regency with using the method of research a qualitative. To measure effectiveness of the management Allocation of Village Funds is a writer trying to fit this research by using the theory put forward by Duncan, namely: Achieving the goal, integration and adaptation. In this study can be described that the management Allocation of Village Funds in 2017 at the Hessa Perlompongan is still not succeeded in creating the improvement of public welfare because there are still problems that impede the achievement of these objectives, such as the amount of funds disbursed from the Government of the to the very limited and a lot of the needs of internal Government of which are filled with the use of Allocation of Village Funds so that no funds are distributed not enough to improve the welfare of society, including the community who works as covered in the Allocation of Village Funds as tutor, the dead bilal, the gravediggers and so forth.